INFLUENCE OF EXHAUST FAN POSITION AND THE ADDITION OF SECONDARY EXHAUST FAN TO CONTROL INDOOR AIR POLLUTION (IAP) INSIDE A PARKING GARAGE - Pramadhony, Pramadhony; Puspitasari, Dewi; Said, Muhammad; Sahim, Kaprawi (Journal of Applied Engineering Science, 2024)
Air pollution has significantly deteriorated air quality in many urban areas, leading to numerous health issues. This pollution is not confined to outdoor environments but also affects indoor spaces, such as parking garages in basements. One major concern is cold-start emissions from idling cars, which produce higher concentrations of pollutants compared to normal hot emissions. Internal Combustion Engine Vehicles (ICEVs) emit cold-start emissions during the first few minutes after ignition. To mitigate this impact, parking operators typically use exhaust fans to replace polluted air with fresh air. However, the design and placement of the exhaust fan should be optimized to ensure a healthy indoor environment and efficient energy use. This research examines the concentration of air pollutants in a parking garage with three idling cars, focusing on the effectiveness of an exhaust fan installed in two different positions: near the parking spaces and near the pathway. Additionally, the research evaluates the impact of the exhaust fan's position and the inclusion of a secondary exhaust fan on carbon monoxide (CO) concentration during cold-start emissions. The results indicate that the primary exhaust fan should be installed in Position A, as it provides better airflow distribution and effectively extracts air pollutants. Improper airflow distribution, observed when the exhaust fan is installed in Position B, results in some measurement points showing high CO concentrations, with the highest average concentration reaching 68.9 ppm. Furthermore, the addition of a secondary exhaust fan helps reduce the average CO concentration and shortens the duration of the cold-start emission effect.
Keywords: indoor air quality, cold-start emission, emission dispersion, parking garage